LRIG1 regulates cadherin‐dependent contact inhibition directing epithelial homeostasis and pre‐invasive squamous cell carcinoma development. Issue 4 (15th February 2013) - Lu, Liwen; Teixeira, Vitor H; Yuan, ZhengQiang; Graham, Trevor A; Endesfelder, David; Kolluri, Krishna; Al‐Juffali, Noura; Hamilton, Nicholas; Nicholson, Andrew G; Falzon, Mary; Kschischo, Maik; Swanton, Charles; et al.
Abstract Epidermal growth factor receptor (EGFR) pathway activation is a frequent event in human carcinomas. Mutations in EGFR itself are, however, rare, and the mechanisms regulating EGFR activation remain elusive. Leucine‐rich immunoglobulin repeats‐1 (LRIG1), an inhibitor of EGFR activity, is one of four genes identified that predict patient survival across solid tumour types including breast, lung, melanoma, glioma, and bladder. We show that deletion of Lrig1 is sufficient to promote murine airway hyperplasia through loss of contact inhibition and that re‐expression of LRIG1 in human lung cancer cells inhibits tumourigenesis. LRIG1 regulation of contact inhibition occurs via ternary complex formation with EGFR and E‐cadherin with downstream modulation of EGFR activity. We find that LRIG1 LOH is frequent across cancers and its loss is an early event in the development of human squamous carcinomas. Our findings imply that the early stages of squamous carcinoma development are driven by a change in amplitude of EGFR signalling governed by the loss of contact inhibition.